THE ROLE OF MOODLE IN EDUCATION: A BIBLIOMETRIC REVIEW - Akbar Nasrum; Made Subawo; Ully Hidayati (USN Kolaka, 2023)
Moodle is a trendy digital learning platform in education widely used to create online courses. Moodle's role in education is crucial because it provides many benefits, including facilitating distance learning, increasing student participation, increasing teaching efficiency, enabling easy assessment, enabling personalized teaching, and so on. There have been many studies onMoodle in the form of articles from year to year. Therefore, in this research, a bibliometric study will be carried out on the roles of Moodle in the world of education, mapping research results, looking at research trends, and looking for possible gaps that can still be studied more deeply. The method used in this research is a Systematic Literature Review using bibliometric analysis with the help of VoS Viewer. The study results show that Moodle is widely used to benefit learning in various fields, especially STEM. Moodle is generally used to digitize learning, including, in this case, the assessment and gamificationprocess in learning.